PRE-SEASON DEPLOYMENT OF IN2CARE® MOSQUITO STATIONS TO CONTROL AEDES AEGYPTI POPULATION IN THE WEST VALLEY REGION OF SAN BERNARDINO COUNTY, CALIFORNIA - Birhanie, Solomon Kibret; Hans, Jacob; Melgoza, Alfonso; Reisinger, Brian; Brown, Michelle Q (Journal of the American Mosquito Control Association, 2025)
The recent geographic expansion of Aedes aegypti poses a significant global public health challenge. In California, these invasive mosquitoes are now present in over 300 cities across 25 central and southern counties. The In2Care® Mosquito Station, which uses biological control agents to target Aedes mosquitoes, has shown promise when integrated into existing integrated vector management strategies. This study evaluated the impact of pre-season deployment of In2Care stations on Ae. aegypti populations. Two cohorts were established: 1 with 17 sites deploying stations pre-season (April-November), and another with 15 sites deploying during peak season (July-November), maintained during 2022-2024. Monthly BG-2 Sentinel trap data showed a significant reduction in Ae. aegypti abundance at pre-season In2Care sites: from 31.2 mosquitoes/trap-night in 2022 to 20.1 in 2023 and 13.2 in 2024, with a year-to-year reduction of 34-36%. Peak-season In2Care sites showed a 24-36% reduction in mosquito abundance four weeks post-deployment. Pre-season In2Care sites maintained 22-34% lower mosquito abundance than peak-season sites. These results demonstrate that early deployment of In2Care stations prior to the mosquito season significantly reduces Ae. aegypti populations and reinforces the existing integrated vector management programs.